Geochemical Soil Survey at Jesenice area, Slovenia - Šajn, Robert; Bidovec, Milan; Gosar, Mateja; Pirc, Simon (Geologija, 1998)
The purpose of geochemical investigations in the Jesenice area was to establish contents and distribution of Chemical elements in soils, and to separate the natural from the man-produced geochemical distributions. Shown and commented are distributions of 21 elements (Al, Ca, Fe, K, Mg, Ti, Ba, Cd, Cr, Cu, Hg, La, Mn, Nb, Ni, Pb, Sc, Th, V, Zn and Zr). Based on comparison of distributions of these elements in soils and urban sediments (household and attic dust) of Slovenia two natural geochemical associations were distinguished in the Jesenice area (Al-Fe-K-Ti-Ba-La-Nb-Sc-Th-V-Zr and soil pH-Ca-Mg), and two associations that were influenced by several centuries of mining and iron making (Cd-Cu-Hg-Mn-Pb-Zn and Fe-Cr-Ni).